If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x(6x + 10) = 320whatisx Reorder the terms: 8x(10 + 6x) = 320whatisx (10 * 8x + 6x * 8x) = 320whatisx (80x + 48x2) = 320whatisx Solving 80x + 48x2 = 320ahistwx Solving for variable 'x'. Reorder the terms: -320ahistwx + 80x + 48x2 = 320ahistwx + -320ahistwx Combine like terms: 320ahistwx + -320ahistwx = 0 -320ahistwx + 80x + 48x2 = 0 Factor out the Greatest Common Factor (GCF), '16x'. 16x(-20ahistw + 5 + 3x) = 0 Ignore the factor 16.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-20ahistw + 5 + 3x)' equal to zero and attempt to solve: Simplifying -20ahistw + 5 + 3x = 0 Reorder the terms: 5 + -20ahistw + 3x = 0 Solving 5 + -20ahistw + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -20ahistw + -5 + 3x = 0 + -5 Reorder the terms: 5 + -5 + -20ahistw + 3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -20ahistw + 3x = 0 + -5 -20ahistw + 3x = 0 + -5 Combine like terms: 0 + -5 = -5 -20ahistw + 3x = -5 Add '20ahistw' to each side of the equation. -20ahistw + 20ahistw + 3x = -5 + 20ahistw Combine like terms: -20ahistw + 20ahistw = 0 0 + 3x = -5 + 20ahistw 3x = -5 + 20ahistw Divide each side by '3'. x = -1.666666667 + 6.666666667ahistw Simplifying x = -1.666666667 + 6.666666667ahistwSolution
x = {0, -1.666666667 + 6.666666667ahistw}
| 30x+17x-58x-24=0 | | 4+2m=5-6m | | (9m+10)2= | | 2z^2-6z+9=0 | | 12x^2+13=85 | | 6+9(x+13)=17 | | x^2+2=2+3*2 | | x^2+x-4=-2.561552813 | | x^3-3x^2+9x=0 | | 9x/2=4.5 | | x^3-3x^2+9=0 | | 9x/2=10 | | 9x/2=1 | | 9x/2=3 | | 81a^2-9= | | 5[u(t)-u(t-1)]-3[u(t-2)-u(t-4)]+0[u(t-4)]= | | x^5+5x^4-2x^3-10x^2+x+5=0 | | 2u(t-1)-5u(t-3)+(t-5)= | | (8x-10x)x=-18 | | (8x-10x)x=-1000000 | | 8x-10x^2=-2x | | 10x-10x^2=-x | | x=2y+10 | | w^2+8w=w(24) | | 6x^2+5x-116=0 | | 21x^3=14 | | (5x-1)(x+3)-(x-5)(5x+1)=40 | | x^2-4x+96=0 | | 7y+5=33 | | x=7x^2+5x-5 | | x(C)=7x^2+5x-5 | | x+2(x^2)=36 |